Food Image of Jammu & Kashmir UT – Viewpoint of Inbound Tourists - Ashish Raina, Dr Varinder Singh Rana, Dr. Arun Singh Thakur (International Journal of Advanced Science and Technology, 2020)
The study aims to conclude the current food image of Jammu Kashmir and its overall satisfaction in the view point of tourists visiting Jammu & Kashmir. Based on the prior studies, responses to a questionnaire with various attributes deciding satisfaction level for local food got recorded from the tourists visiting Jammu Kashmir with different reasons. After statistical application of responses from tourists, the food from the region is identified as core value for tourists with another major attributes as specialty and uniqueness. Quality and value of food and convenience in eating were given more emphases then eating atmosphere and food as a product of culinary tourism. Multiple regressions came up with the fact that attributes of food and food image of destination effects tourist satisfaction at a destination. Results of the study have been circulated to managers and owners of food establishments to get better prepared in serving tourists visiting Jammu and Kashmir UT.